Hybrid Caffeic Acid-Based DHFR Inhibitors as Novel Antimicrobial and Anticancer Agents - Renu Sehrawat; Ritu Pasrija; Priyanka Rathee; Deepika Kumari; Anurag Khatkar; Esra Küpeli Akkol; Eduardo Sobarzo-Sánchez (MDPI AG, 2024)
A novel series of 1,2,4-triazole analogues of caffeic acid was designed, synthesized, characterized, and assessed for their capacity to inhibit DHFR, as well as their anticancer and antimicrobial properties. A molecular docking analysis was conducted on DHFR, utilizing PDB IDs 1U72 and 2W9S, aiming to design anticancer and antimicrobial drugs, respectively. Among all the synthesized derivatives, compound CTh7 demonstrated the highest potency as a DHFR inhibitor, with an IC50 value of 0.15 μM. Additionally, it exhibited significant cytotoxic properties, with an IC50 value of 8.53 µM. The molecular docking analysis of the CTh7 compound revealed that it forms strong interactions with key residues of homo sapiens DHFR such as Glu30, Phe34, Tyr121, Ile16, Val115, and Phe31 within the target protein binding site and displayed excellent docking scores and binding energy (−9.9; −70.38 kcal/mol). Additionally, synthesized compounds were screened for antimicrobial properties, revealing significant antimicrobial potential against bacterial strains and moderate effects against fungal strains. Specifically, compound CTh3 exhibited notable antibacterial efficacy against Staphylococcus aureus (MIC = 5 µM). Similarly, compound CTh4 demonstrated significant antibacterial activity against both Escherichia coli and Pseudomonas aeruginosa, with MIC values of 5 µM for each. A docking analysis of the most active antimicrobial compound CTh3 revealed that it forms hydrogen bonds with Thr121 and Asn18, a π-cation bond with Phe92, and a salt bridge with the polar residue Asp27.